2019
DOI: 10.3390/su11072087
|View full text |Cite
|
Sign up to set email alerts
|

Determining Appropriate Lane-Changing Spacing for Off-Ramp Areas of Urban Expressways

Abstract: Congestion has become a significant issue in recent years and has greatly affected the efficiency of urban traffic operation. Random and disorderly lane-changing behavior greatly reduces traffic capacity and safety. This paper is mainly concerned with the relationship of lane-changing spacing intervals provided by off-ramp facilities and traffic flow conditions. Through field investigations in Beijing, several typical lane-changing behaviors at off-ramp areas are analyzed. By using field traffic data and actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In the diverging scenario a significant effort was invested to develop lanechanging strategies that minimize congestion and increase safety. Huang et al conducted a series of simulations [8] to investigate the cause of heavy congestions in two Beijing off-ramp areas. It was found that lane-spacings and the lane-changing spacings are the main factors that define traffic throughput, safety and efficacy.…”
Section: Vehicular Controlmentioning
confidence: 99%
“…In the diverging scenario a significant effort was invested to develop lanechanging strategies that minimize congestion and increase safety. Huang et al conducted a series of simulations [8] to investigate the cause of heavy congestions in two Beijing off-ramp areas. It was found that lane-spacings and the lane-changing spacings are the main factors that define traffic throughput, safety and efficacy.…”
Section: Vehicular Controlmentioning
confidence: 99%
“…Hence, the complex traffic feature of multilane roadways, specifically the lane change behavior, may not be well captured when modeling them as a single-lane traffic stream [13,14]. It is also known that frequent LC events result in traffic flow instabilities as a result of the drop in capacity as well as the formation and propagation of stopand-go waves [15][16][17][18][19][20].…”
Section: Cell Transmission Model and Ctm Based Lane Change Modelmentioning
confidence: 99%
“…e results demonstrated that the total throughput decreased slowly with the increase of the weaving ratio. Huang et al [29] studied the relationship between off-ramp lane-changing spacing and traffic congestions on urban expressways and tested the impact of different densities of traffic and off-ramp ratios on the congestion.…”
Section: Introductionmentioning
confidence: 99%